METHOD OF PROJECTS IN EDUCATIONAL ACTIVITIES OF JUNIOR SCHOOLCHILDREN - L.I. Petryshyna (Academy of Cognitive and Natural Sciences, 2010)
Presenting methods elaborate with use of projects method for pupils primary-school.